Civil responsability in the context of school harassment in Chile - Astudillo González, Camila; Figueroa Mendoza, Mauricio; Miranda Santana, Paulina (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The objective of this paper is to determine the type of civil liability that is generated, be it contractual or non-contractual, the active subjects to whom it could be attributed, whether they are the authors themselves, their parents or the school itself, and the applicable sanctions in the if said responsibility becomes effective in contexts of school violence within the various educational establishments in Chile.